2018
DOI: 10.1101/462713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prolonged quiescence delays somatic stem cell-like division inCaenorhabditis elegansand is controlled by insulin signalling

Abstract: Cells can enter quiescence in adverse conditions and resume proliferation when the environment becomes favorable. Prolonged quiescence comes with a cost, reducing the subsequent speed and potential to return to proliferation. Here, we show that a similar process happens during Caenorhabditis elegans development, providing an in vivo model to study proliferative capacity after quiescence. Hatching under starvation provokes the arrest of blast cell divisions that normally take place during the first larval stage… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Worms hatched from vitellogenin-depleted embryos, achieved by maternal knockdown of either vitellogenins or rme-2 , show an increased frequency of these defects, including sterility, as do the progeny of young mothers (Perez et al, 2017; Jordan et al, 2019). Accordingly, progeny of young mothers, with reduced vitellogenin titers, showed premature signs of aging (Roux et al, 2016) during L1 starvation (Olmedo et al, 2018). Increased embryonic vitellogenin titers lead to reduced insulin-like signaling in progeny, which mediates the supression of germline defects after recovery from L1 starvation (Jordan et al, 2019) and may also explain the supression of aging in starved L1s.…”
Section: Vitellogenins In C Elegans Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Worms hatched from vitellogenin-depleted embryos, achieved by maternal knockdown of either vitellogenins or rme-2 , show an increased frequency of these defects, including sterility, as do the progeny of young mothers (Perez et al, 2017; Jordan et al, 2019). Accordingly, progeny of young mothers, with reduced vitellogenin titers, showed premature signs of aging (Roux et al, 2016) during L1 starvation (Olmedo et al, 2018). Increased embryonic vitellogenin titers lead to reduced insulin-like signaling in progeny, which mediates the supression of germline defects after recovery from L1 starvation (Jordan et al, 2019) and may also explain the supression of aging in starved L1s.…”
Section: Vitellogenins In C Elegans Physiologymentioning
confidence: 99%
“…Additionally, increased vitellogenin in the embryos of older mothers explains a shortening of the time taken to reach adulthood after hatching, even in the absence of starvation (Perez et al, 2017). It was shown that young maternal age and embryonic vitellogenin depletion by rme-2 RNAi led to delayed adulthood after feeding in previously-starved L1s not by accelerating the overall rate of development but specifically prolonging the time required to initiate development from the L1 stage (Olmedo et al, 2018). High levels of yolk provisioning thus improve offspring outcomes, in both favorable and unfavorable conditions.…”
Section: Vitellogenins In C Elegans Physiologymentioning
confidence: 99%
“…A recent study found that the developmental delay arising after recovery from starvationinduced L1 arrest occurrs not due to a slowing of developmental rate, but rather due to a delay in the initiation of post-embryonic development upon feeding. 44 This led us to hypothesize that pheromone exposure in the parents may affect the relative timing of post-embryonic developmental initiation in progeny somatic or germline tissues, rather than their relative rate of development. Furthermore, this hypothesis could explain the intergenerational germline delay as a latent effect of maternal control over an early developmental event, whose effects manifest in progeny up to adulthood.…”
Section: Germline Delay Results From Delayed Initiation Of Postembryonic Developmentmentioning
confidence: 99%
“…These results suggest that the delay observed is largely due to a delay in developmental initiation rather than a slowing of developmental rate. 44 The phenotypes of the first progeny hatching on a fresh plate, laid shortly after parents were transferred, resembled those of worms hatched on the used plate, suggesting that it was an intergenerational effect of parental environment, rather than the environment encountered upon hatching, that determined the phenotype of progeny (Figures S1C-S1F). To .…”
Section: Exposure Of Parents To Pheromone Induces Germline Delay In Progenymentioning
confidence: 91%
“…Previous studies demonstrated that starvation leads to a reduction of daf-2 -mediated signaling as DAF-16 activity is required for starvation survival as well as maintaining germline quiescence (Baugh and Sternberg, 2006; Hibshman et al, 2017). Furthermore, upon feeding, daf-2 transcription is reduced, and DAF-16 activity is necessary to promote growth and development (Chen and Baugh, 2014; Kaplan et al, 2019; Olmedo et al, 2020) suggestive of a more nuanced daf-2 regulation. We propose a model that the prolonged lack of food during L1 arrest leads to modest reduction of daf-2 signaling along with the gradual decline in mitochondrial activity while sustaining foraging, depletion of mtDNA, mitochondrial fragmentation and reduced respiration.…”
Section: Discussionmentioning
confidence: 99%